The Effect of Stock Ownerships Structure on the Disclosure of Corporate Social Responsibility (Case Study on Mining Company Listed in Indonesia Stock Exchange) - Lukyta Sari A.F (Lembaga Intelektual Muda (LIM) Maluku, 2022)
Corporate social responsibility is the expression as one of the media to show concern and corporate social activities for the people in the area. So that the people feel safe havens in use production companies. This will affect corporate image so that indirectly will have an effect on to benefit that will be obtained. Based on this matter this research examines the influence company ownership structure that reflected on the institutional ownership, management ownership, and foreign ownership of extensive corporate social responsibility is the expression. Samples in this research is 30 mining companies listed in Indonesia Stock Exchange period of 2008-2012 by using purposive sampling. The method of analysis is quantitative analysis. The results of this study indicate that the variable that affect disclosure of corporate social responsibility is institutional ownership and foreign ownership. While variables that did not affect disclosure of corporate social responsibility are management ownership.